2022
DOI: 10.1002/solr.202100880
|View full text |Cite
|
Sign up to set email alerts
|

Multistrategy Toward Highly Efficient and Stable CsPbI2Br Perovskite Solar Cells Based on Dopant‐Free Poly(3‐Hexylthiophene)

Abstract: All‐inorganic perovskites have attracted substantial interest due to their outstanding thermal stability. However, the device performance is still inferior to the typical organic–inorganic counterparts because of the unsatisfying phase stability and defects of the inorganic perovskite films. Herein, a multistrategy to optimize CsPbI2Br perovskite solar cells (PSCs) based on dopant‐free poly(3‐hexylthiophene) (P3HT) by applying thienylmethylamine acetate additive to enhance the α phase stability and passivate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…The most common one is acetate ion (CH 3 COO − , Ac − ). [39,44,101,116,133] For example, Liu et al [44] demonstrated that Ac − in the halogen site of CsPbI 2 Br could optimize the film morphology and improve crystallinity of CsPbI 2 Br perovskite, thus, reducing the defect concentration and increasing the carrier lifetime of the modified film. Moreover, density functional theory (DFT) calculations showed that Ac − induced a distortion of the perovskite structure along with a deviation of the PbIPb bond angle from the ideal 180° (Figure 7a).…”
Section: Anionic Additivesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common one is acetate ion (CH 3 COO − , Ac − ). [39,44,101,116,133] For example, Liu et al [44] demonstrated that Ac − in the halogen site of CsPbI 2 Br could optimize the film morphology and improve crystallinity of CsPbI 2 Br perovskite, thus, reducing the defect concentration and increasing the carrier lifetime of the modified film. Moreover, density functional theory (DFT) calculations showed that Ac − induced a distortion of the perovskite structure along with a deviation of the PbIPb bond angle from the ideal 180° (Figure 7a).…”
Section: Anionic Additivesmentioning
confidence: 99%
“…Other studies have also proved that Ac − induced smaller perovskite grain size, passivated grain boundaries, and stabilized the crystal lattice. [39,101,133] Han et al studied in situ passivation of Ac − in CsPbI 2 Br PSCs. [39] In this work, PbO was formed in situ at the grain boundary by decomposing Pb(Ac) 2 at high annealing temperature.…”
Section: Anionic Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding effect between BTCIC‐4Cl and CsPbI 2 Br/P3HT could significantly affect the performance and stability of the device. [ 62 ]…”
Section: Interface Modifiersmentioning
confidence: 99%
“…In order to solve this problem, interfacial engineering is widely applied. For example, implementing BTCIC-4Cl 29 or copper(I) thiocyanate (CuSCN) 30 at perovskite/P3HT interface to passivate the surface defects of perovskite can give a reported e ciency of ~ 16% for CsPbI 2 Br-based devices. Seo et al introduced a layer of n-hexyl trimethyl ammonium bromide (HTAB) to modulate the packing of P3HT and obtained a PCE over 22% for (FAPbI 3 ) 0.95 (MAPbBr 3 ) 0.05 -based device 26 .…”
Section: Introductionmentioning
confidence: 99%